CURRENT APPROACHES TO PREVENTING CHILDHOOD OBESITY - A. A. Kamalova (Rossijskij Vestnik Perinatologii i Pediatrii, 2017)
Obesity prevention is a priority in health care. The paper gives the results ofstudies of the prevention of overweight and obesity in childhood. It discusses specific practical recommendations concerning antenatal prophylaxis, a balanced diet, complementary food, and infant feeding tactics. Inclusion of functional foods as an important component of dietary measures to prevent obesity is warranted.